‘It's mostly about the job' - putting the lens on specialist rural retention - Penny Allen; Jenny May; Robert Pegram; Lizzi Shires (James Cook University, 2020)
Introduction: Rural health services throughout the world face considerable challenges in the recruitment and retention of medical specialists. This research set out to describe the factors that contribute to specialist workforce retention and attrition in a health service in rural Tasmania, Australia. Methods: This qualitative study utilised in-depth interviews with 22 medical specialists: 12 currently employed by the service and 10 who had left or intended to leave. Interview transcripts were thematically analysed to identify professional, social and location factors influencing retention decision-making. Results: Professional and workplace factors were more important than social or location factors in retention decision-making. Tipping points were excessive workloads, particularly on-call work, difficult collegial relationships, conflict with management, offers of more appealing positions elsewhere, family pressure to live in a metropolitan area, educational opportunities for children and a lack of contract flexibility. Inequitable workload distribution and the absence of senior registrars contributed to burnout. Financial remuneration was not a primary factor in retention decision-making, however, there was acknowledgement of the need to ensure equitable pay scales, flexible employment contracts including statewide positions and increased CPD payments/leave. Specialists who had autonomy in determining their preferred work balance tended to stay, as did those who had family or developed social connections within the area, rural backgrounds and a preference for rural living. Conclusion: To improve specialist workforce retention, rural health services should ensure a professionally rewarding, harmonious work environment, without onerous out-of-hours demands and where specialists feel valued. Specialists should have autonomy over workloads, flexible contracts, appropriate financial remuneration and enhanced access to CPD. New specialists and their families should have additional support to assist with social integration.